Parental emotionality and power relations in heritage language maintenance: experiences of Chinese and African immigrant families in Australia - Wang, Yining; Williams Tetteh, Vera; Dube, Sithembinkosi (Frontiers in Psychology, 2023)
Emotionality is increasingly given prominence in the field of language acquisition and socialization in migration contexts. This cross-sectional study explores the emotional experiences of Chinese and African immigrant families in their practices of maintaining their children's heritage languages. We used open-ended interviews, field notes from informal conversations and observations, photographic evidence of children's literacy practices, and language portrait (LP) descriptions, to collect data. Results from an ethnographic analysis of the data revealed a whole range of negative and positive parental emotions (e.g., anxiety, loss, shame vs. enjoyment, accomplishment, and pride), in the discourse of maintaining heritage and minority languages. We discuss the language emotions, whether positive or negative, in light of language ideologies, which specifically points to the significance of profit discourse in the formation of family language policies (FLPs). This materialistic valorization reveals the complexities of power relations between English and minority languages, between Chinese and African languages, and within various Chinese and African languages. Consequently, the distinct hierarchies between English and minority languages and the hidden layers within minority languages further legitimate diasporic ideologies of Chinese and African parents in terms of the emotionality associated with prioritizing, maintaining, and forgoing languages. These findings suggests that language emotionality is of vital importance to the psycho-social wellbeing of immigrant families and has practical implications for policymakers and heritage language research.